A New Era of Tax Enforcement: From 'Big Stick' to Responsive Regulation - Leviner, Sagit (2009)
This Article explores the economics of crime and compliance as the dominant approach to U.S. tax enforcement of the past three and a half decades. It evaluates the key advantages and disadvantages of the economic model as well as its application to tax. The Article then addresses the multiplicity of taxpayer behavior and the need and prospect of balancing the economically conceived methods of detection and punishment against other, more cooperative, means and developing a broader approach to tax enforcement more generally. The Article explores responsive regulation as a case study for an alternative method to tax enforcement that heavily draws on the economic paradigm but also supplements this approach with other theories, particularly those involving taxpayer identity, conflict escalation, and procedural justice. The Article suggests that this broader, more balanced, and closely tailored method of regulating responsively may enable regulators to draw on the advantages of the economic model while alleviating some of its drawbacks. Responsive regulation may therefore constitute a superior method for regulating tax compliance